Facilities and bureaucratic process of Malaysian local authorities influenced on micro enterprises business performance - Jasin, Harun; Saud, Mohammad Basir; Md Isa, Mohd Azwardi; Hussain, Fawad (2016)
In this paper, the researcher will determine how the local authorities influence on Micro Enterprises (MEs) business performance in term of providing facilities and bureaucratic process which plays an important role for the enhancement and development of Malaysian MEs.In addition, the integration of the existing business support by government through its agencies in Malaysia could create a cohesive environment for supporting MEs business growth.This study had used 457 completed and returned questionnaires by MEs from northern region of Malaysia.The findings have indicated that bureaucratic process has no significant relationship on MEs business performance. However, facilities do had a significant influence on MEs business performance.This might be because MEs, they themselves do not really concern about bureaucratic process of local authority. On the other hands, what more matters for MEs is to what extend the facilities as well as infrastructure provided by local authority for customers accessing to the business area, customer’s comfortability and attractive environment that could enhance their business operations.